The science of chemistry / Ira M. Freeman - Freeman, Ira M. [et. al] (New York State: Random House Science library, 1954)
How chemistry began, what our world is made of, the chemist builds molecules, oil- the chemist' s treasure chest, the carbons combine, the chemist in the steel mill, some other useful metals, fuel for the human enhine, chemicals that cure, chemistry on the farm, fibers and plastics, rubber, more good things from chemistry.
Índice, ilustrada, dramática
Col. Educ
Keywords: 1. QUIMICA FISICA 2. SCIENCE CHEMISTRY 3. CHEMIST MOLECULAS4. EDUCACIÓN